Numerical analysis of storm surge overtopping along Tacloban-Palo-Tanauan tide embankment due to Typhoon Haiyan 2013 - Rizabal, Karl Derrick S.; Cruz, Eric C.; Villalba, Imee Bren O. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Last November 2013, the coasts of Tacloban, Palo, and Tanauan was leveled by the storm tide brought by typhoon Haiyan. To prevent the same thing from happening, the Department of Public Works and Highways consulted Japan International Cooperation Agency for solutions and came up with the Road Heightening and Tide Embankment Project. The main purpose of the study is to determine if the vertical design height of the tide embankment to be constructed along the coasts of Tacloban, Palo, and Tanauan will be overtopped by Typhoon Haiyan storm tide. By knowing the overtopping points, essential facilities for recovery and order during times of crisis, such as hospitals and government offices, will be established on places far from overtopped sections such that they would not be severely affected by the effects of typhoon. Planning for safety measures in Tacloban, Palo, and Tanauan against strong typhoons will also be improved by learning how the storm surge behave when there is a tide embankment present. To achieve this, a numerical model is made using ADCIRC, whose focus is to get the overtopping points along the tide embankment. In this numerical model, waves are not modeled and the inundation on the landward side of the tide embankment is disregarded. First, a numerical model was applied to the domain. Then, Manning's roughness coefficients of the mesh are calibrated and validated by comparing the simulated tidal heights with the actual and forecast data from NAMRIA and WXTide and resulted to an RMS error of 0.102m. Moving on to the typhoon simulation, the simulation was able to finish without instabilities by changing the primitive weighting in continuity equation for land areas. The simulation showed that all points in the tide embankment have an overtopping height ranging from 0.77 m to 3.19 m. Further studies may be conducted on the structural and geotechnical stabilities of the tide embankment may be done for added safety. The time series of the points adjacent to the initial overtopped points for each section was obtained and labeled with corresponding monitoring points. The time series obtained was summarized and showed that overtopping starts at the mouth of the bay and moves toward the inner parts of the bay. It was also shown that the duration of overtopping is longer at the mouth of the bay than the inner part of the bay. An effective disaster mitigation plan may be procured from the observations mentioned.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Storm surges; Typhoon Haiyan, 2013.